Beyond the valley of thorns - Carman, Patrick (New York : Orchard Books, 2005)
When thirteen-year-old Alexa embarks on a mysterious quest, she finds her old friends Yipes the little man, Murphy the squirrel, Odessa the wolf, and Squire the hawk have been designated to help her.
Keywords: Human-animal communication -- Fiction; Magic -- Fiction; Adventure and adventurers -- Fiction